The complement regulatory protein CD46 serves as a novel biomarker for cervical cancer diagnosis and prognosis evaluation - Yu, Jun-Hui; Yuan, Hao-Bo; Yan, Zi-Yi; Zhang, Xia; Xu, Hui-Hui (Frontiers in Immunology, 2024)
Background: CD46 has been revealed to be a key factor in malignant transformation and cancer treatment. However, the clinical significance of CD46 in cervical cancer remains unclear, and this study aimed to evaluate its role in cervical cancer diagnosis and prognosis evaluation.Methods: A total of 180 patients with an initial diagnosis of cervical cancer were enrolled at Taizhou Hospital of Zhejiang Province, China. The plasma levels of soluble CD46 (sCD46) and the expression of membrane-bound CD46 (mCD46) were detected by enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry (IHC), respectively.Results: CD46 was found to be significantly upregulated in cervical cancer tissues vs. normal tissues, while no CD46 staining was detected in paired adjacent noncancerous tissues. CD46 staining was more pronounced in cancer cells than in stromal cells in situ (in tissues). Moreover, the plasma levels of sCD46 were able to some extent discriminate between cancer patients and healthy women (AUC=0.6847, 95% CI:0.6152-0.7541). Analysis of Kaplan-Meier survival curves revealed that patients with low CD46 expression had slightly longer overall survival (OS) than patients with high CD46 expression in the tumour microenvironment, but no significant difference. Univariate Cox regression analysis revealed that CD46 (P=0.034) is an independent risk factor for OS in cervical cancer patients.The present study demonstrated that cervical cancer patients exhibit aberrant expression of CD46, which is closely associated with a poor prognosis, suggesting that CD46 plays a key role in promoting cervical carcinogenesis and that CD46 could serve as a promising potential target for precision therapy for cervical cancer.